Not sky-high. - Oppenheim, Jeremy; Beinhocker, Eric.; Farrell, Diana
We can dramatically reduce greenhouse gases and grow economy for less than we think.
Keywords: Greenhouse effect, Atmospheric; Climatic changes; Energy conservation; CLean-energy economy